IMPLEMENTASI SISTEM INFORMASI MANAJEMEN BERBASIS KURIKULUM CINTA DALAM MENINGKATKAN TATA KELOLA PENDIDIKAN ISLAM: STUDI KASUS DI MTsN 1 PALEMBANG: indonesia - Baktina Damayanti; Ahmad Zainuri; Afriantoni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the importance of integrating Management Information Systems (MIS) with value-based curriculum, particularly the love-based curriculum, in improving Islamic education governance. Digital transformation in Islamic educational institutions often focuses on administrative aspects and has not fully accommodated value dimensions. Therefore, this study aims to analyze the implementation of MIS based on the love-based curriculum in enhancing Islamic education governance at MTsN 1 Palembang. This research employs a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings indicate that the implementation of MIS has improved effectiveness, efficiency, transparency, and accountability in educational management. However, the integration of love-based curriculum values into the information system remains suboptimal and tends to be cultural rather than systemic. This study concludes that an integrative model combining technological and value-based aspects is needed in Islamic education management systems. The contribution of this research lies in developing a value-based MIS concept as a novel approach to improving the governance of Islamic education.